Adjoint and Trivial Cohomologies of Nilpotent Complex Lie Algebras of Dimension - L. Magnin (International Journal of Mathematics and Mathematical Sciences)
We present tables for adjoint and trivial cohomologies of complex nilpotent Lie algebras of dimension . Attention is paid to quadratic Lie algebras, Poincaré duality, and harmonic cocycles.